Cardiac Involvement in Facioscapulohumeral Muscular Dystrophy (FSHD) - Allison Ducharme-Smith (Frontiers in Neurology, 2021)
Background: Facioscapulohumeral muscular dystrophy (FSHD) is one of the most common muscular dystrophies and predominantly affects facial and shoulder girdle muscles. Previous case reports and cohort studies identified minor cardiac abnormalities in FSHD patients, but their nature and frequency remain incompletely characterized.Methods: We reviewed cardiac, neurological and genetic findings of 104 patients with genetically confirmed FSHD.Results: The most common conduction abnormality was complete (7%) or incomplete (5%) right bundle branch block (RBBB). Bifascicular block, left anterior fascicular block, complete atrioventricular block, and 2:1 atrioventricular block each occurred in 1% of patients. Atrial fibrillation or flutter were seen in 5% of patients. Eight percent of patients had heart failure with reduced ejection fraction and 25% had valvular disease. The latter included aortic stenosis in 6% (severe in 4% and moderate in 2%) and moderate aortic regurgitation in 8%. Mitral valve prolapse (MVP) was present in 9% of patients without significant mitral regurgitation. There were no significant associations between structural or conduction abnormalities and age, degree of muscle weakness, or size of the 4q deletion.Conclusions: Both structural and conduction abnormalities can occur in FSHD. The most common abnormalities are benign (RBBB and MVP), but more significant cardiac involvement was also observed. The presence of cardiac abnormalities cannot be predicted from the severity of the neurological phenotype, nor from the genotype.